Geological Drawing and the Artistic (Re)interpretation of Rurality During the Spanish Avant-garde (diségno, 2026)
The aim of this research is to analyse the presence of the geological imagery in the context of the Spanish artistic avant-garde, and its role in the aesthetic-ideological (re)interpretation of the rural Castilian landscape. Specifically, we refer to the creative process led by the so-called Vallecas School (1927-1933) and its two most prominent artists: Alberto Sánchez and Benjamín Palencia. To this end, an exhaustive review has been carried out of all geological publications from the period (1912-1936) in order to document the visual relationships between scientific drawings and those produced by both artists; in some cases, for the first time in the study of this phenomenon of convergence between scientific and aesthetic landscape. We shall also examine how this synapse was not limited to the visual representation of the rural nature; for, in tune with the political climate of the time, it also involved a political commitment to a shared area of action (the rural territory) which geologists and artists from Vallecas School –each from their respective disciplines– perceived as a symbolic space for an alternative form of social progress through rural nature, dissident to the dominant urban-technological-bourgeois modernity.
Keywords: Vallecas School; geology; territory; landscape; rural